Composition of Wireless Sensor Module for Vanet Applications - Patel, Aayushi; G, Shilpa; P N, Vidyashree; N, Thangadurai (International Journal of Engineering and Technology, 2018)
In Vehicular Ad-hoc Network (VANET) field enormous research is done recently. VANET consists of dynamic nodes in larger numbers which are mobile nodes over an area. These VANET applications should be thoroughly verified before deployment. To test these technologies in real time is not feasible which involves lot of safety issues; various reports of the testing canâ€™t be generated. To overcome this limitation can carry out simulation of VANET in the virtual environment. The network simulation is gift in this research environment. Simulation of VANET is divided into two categories (i) Traffic simulation which generates of traffic movement, defines the mobility model for vehicle also creating traffic movement and (ii) Network simulation generates communication protocols by inter communicating vehicle.Â Â